Radio modelling of the brightest and most luminous non-thermal colliding-wind binary Apep. Issue 1 (18th October 2021) - Bloot, S; Callingham, J R; Marcote, B
ABSTRACT: Apep is the brightest and most luminous non-thermal colliding-wind binary by over an order of magnitude. It has been suggested from infrared observations that one of the Wolf–Rayet stars in Apep is launching an anisotropic wind. Here we present radio observations of Apep from 0.2 to 20 GHz taken over 33 yr. The spectrum reveals an extremely steep turnover in the flux density at low frequencies, where the flux density decreases by two orders of magnitude over only 325 MHz of bandwidth. This exponential decline is best described by free–free absorption, with a turnover frequency at 0.54 ± 0.01 GHz. Above the turnover, the spectrum is well described by a power-law and a high-frequency cut-off likely caused by inverse-Compton cooling. The light curve of Apep shows significant variation over the observing period, with Apep brightening by over 50 mJy in a span of 25 yr at 1.4 GHz. Models that assume spherical winds do not replicate all of the structure evident in the radio light curve. We derived a model that allows one of the winds in the system to be anisotropic. This anisotropic model recovers most of the structure of the light curve and is a significantly better statistical fit to the data than the spherical wind model. We suggest such a result is independent support that one of the Wolf–Rayet stars in Apep is launching an anisotropic wind. If the anisotropic wind model is correct, we predict a ∼25 per cent decrease of the 1.4 GHz flux density of Apep over the next 5 yr.